Effects of Zilpaterol hydrochloride feeding duration on color of beef and Holstein semimembranosus steaks packaged in PVC and MAP systems - Gunderson, Jennifer Ann (Kansas State University, 2009)
The objective of this study was to determine the effects of Zilmax® feeding duration (7.56 g/ton Zilmax for 0, 20, 30, or 40 d) on color development and stability of crossbred beef (B) and Holstein (H) semimembranosus (SM) steaks packaged in polyvinyl chloride overwrap (PVC), high-oxygen (80% O2, 20% CO2, HiOx) modified atmosphere packaging (MAP), and low-oxygen (0.4% CO, 30% CO2, 69.6% N2, LoOx) MAP. A 7.62-cm thick portion from beef and Holstein SM muscles (n = 120 total, 30 from each feeding duration) was removed, vacuum packaged, and stored until d 21 when two, 2.54-cm thick steaks were cut, overwrapped with PVC, and placed into retail display for 0 or 3 d. On d 10, the remaining muscle of the SM was enhanced, and five, 2.54-cm thick steaks were cut and assigned to 0, 3, or 5 d (HiOx) and 0 or 9 d (LoOx) of display. Measurements taken on the deep (DSM) and superficial (SSM) portions were: pH, L*, a*, b*, hue angle, and saturation indices, initial color, display color, and discoloration. No Diet × Display Day (P > 0.05) interaction occurred for display color or discoloration scores of B steaks in PVC. On d 1, PVC 30 d H steaks were brighter (P < 0.05) than 40 d H steaks in PVC; no differences (P > 0.05) in H PVC display color due to diet occurred on d 0, 2, and 3. For steaks in HiOx, the DSM of 20 and 30 d B steaks on d 4 and the DSM of 20 d B steaks on d 5 was brighter (P < 0.05) red than 40 d Zilmax B DSM. HiOx 20 d H steaks were darker red (P < 0.05) on d 5 of display and more discolored (P < 0.05) on d 3 to 5 than HiOx H steaks from all other diet regimens. For LoOx, 30 d B steaks were brighter (P < 0.05) red than 0 or 40 d steaks on d 0 and 9 of display. The DSM and SSM of LoOx H steaks from cattle fed Zilmax tended (P > 0.05) to be brighter red than control H steaks through 9 d of display. In conclusion, both HiOx and LoOx minimized color differences due to SM muscle areas. Feeding B cattle Zilmax for 20 or 30 d yields steaks equal to or better in color traits than cattle fed 0 or 40 d when packaged in PVC, HiOx, or LoOx. H steaks in LoOx had slight benefits in color stability when cattle were fed Zilmax for any duration, whereas H steaks in PVC had color advantages with only the 20 and 30 d durations. Packaging 20 d H steaks in HiOx resulted in less desirable color characteristics than all other feeding treatments. Keywords: zilpaterol, beef, Holstein, display color, modified atmosphere packaging, semimembranosus
Keywords: Zilpaterol; Display color; Beef; Modified atmosphere packaging; Holstein; Semimembranosus; Agriculture, Food Science and Technology (0359)